Experiencing Food, Designing Dialogues: Proceedings of the 1st International Conference on Food Design and Food Studies (EFOOD 2017), Ricardo Bonacho, Alcinda Pinheiro de Sousa, Cláudia Viegas, João Paulo Martins, Maria José Pires and Sara Velez Estêvão (eds) (2017). (1st August 2020) - Ilieva, Rositsa T.
Experiencing Food, Designing Dialogues: Proceedings of the 1st International Conference on Food Design and Food Studies (EFOOD 2017), Ricardo Bonacho, Alcinda Pinheiro de Sousa, Cláudia Viegas, João Paulo Martins, Maria José Pires and Sara Velez Estêvão (eds) (2017)Leiden: CRC Press, 174 pp., ISBN 978-1-13857-538-7, h/bk, £120